FREE TRADE AGREEMENTS IN THE WORLD TRADE SYSTEM: BENEFITS AND MODELS - Тетяна Циганкова; Ольга Яценко; Тетяна Тананайко; Ганна Солодковська; Вікторія Олефіренко; Анна Іщенко (Фінансово-кредитна діяльність: проблеми теорії та практики)
It is indicated that one of the characteristic features of the modern trade system is the rapid growth of the number of regional trade agreements, which, in turn, causes asymmetry in the dominance of regional cross-border trade rules over multilateral ones. The main advantages for countries from participating in regional trade agreements have been identified: the possibility of excluding "vulnerable sectors" from the agreement; the ability to independently choose partners in negotiations; the use of the principle of "reciprocity" is more effective compared to the World Trade Organization, the possibility of forming the image of a regional leader; within the framework of such agreements, it is possible to carry out "experimental application" of certain new measures in the field of trade, which, if successfully tested, can be tried to be applied in general mode; the possibility of attracting more foreign investments by developing countries that are not regional leaders. After examining the degree of involvement of countries in concluding regional trade agreements for the presence of regional asymmetries, a significant difference was identified from the maximum involvement of the countries of the European region (on average 33.2 agreements per country) and the countries of Africa (2.7) and the Middle East (3.9). It is proposed that one of the vectors of the development of Ukraine's foreign economic policy should be the expansion of the scope of current and future regional trade agreements to the sphere of services, e-commerce and investments, given the potential, their compliance with the global trends of the trading system, as well as the ability of Ukraine to become a significant player in a number of markets for services and trade in digital products, taking into account the availability of an up-to-date legal framework on these issues. It was determined that 50% of Ukraine's commodity exports during 2016-2021 took place within the framework of the preferential regime provided for by key free trade agreements. According to the results of the proposed forecast of such exports for the period 2021-2023, using the method of time series analysis, it was confirmed that the corresponding dependence will only grow (export volumes within the framework of free trade agreements will grow by 3 percent annually, while total exports by 2%).